Dynamical behavior of quantum-dot laser - Oleiwi, M.O. (University of Thi-Qar Journal of Science, 2014)
In this work we have investigated the dynamical properties of InAs/InGaAs laser emitting 1.3 m pumped by injection current density of fast rise and falling times with a duration of 5ns . In (capture) and out (escape) scattering rates of electrons and holes are studied against temperature, injection current density, Auger coefficient .Scattering times are studied against carrier reservoir loss coefficient , injection current density and temperature. Temporal behaviorof photons density against injection current density is given too.